Sustainability Hermeneutics - Nilsen, Tina D. (Biblical interpretation, 2023)
Ecological issues are not just planet-related issues; they are also people-related issues, and vice versa, as the UN’s 2030 Agenda implies. Hence, ecological aspects in biblical studies should also be studied in relation to social justice, whether this be liberation from oppression, indigenous rights, postcolonialism/neo-colonialism, gender, health, poverty or other. I propose sustainability hermeneutics as the name of an approach which combines perspectives on the environment (ecology), equity (society) and economy. In this article, I emphasise theoretical aspects in developing this new approach, as I discuss different definitions of sustainability and aspects of sustainability theory and show how these may be applied to hermeneutics. I clarify the aims and contributions of sustainability hermeneutics and suggest possible methods and potential material. As an illustration, I present a case study of sustainability hermeneutics applied to a biblical text.